Perspektif guru di SMA Katolik Rex Mundi Manado mengenai upaya pencegahan kekerasan terhadap perempuan - Jayalaksmi, Ni Made Putri; Ottay, Ronald; Sapulete, Margareth; Porajow, Zwingly C. J. G. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Objective: This study aims to get the prespective involve knowledge and attitudes of teachers at SMA Katolik Rex Mundi Manado on prevention of violence against women (VAW). Design: This research is a qualitative descriptive study. The data collection was done by focus group discussion (FGD) and followed with in-depth interview.Tthe location of study was at SMA Katolik Rex Mundi, South Wenang, Manado. There were 11 senior teachers who were the informans. Results: Teacher thinks VAW is an action that cross the line and suffering to women. Most of VAW is intimate partner violence with multifactorial cause. their opinion is teacher has many roles in the prevention of VAW such as setting a good example, shaping student morality up to give little guidances in learning time. Conclusions: Teachers from a range background understand what is VAW, factors associated with VAW and understand what their roles to prevent VAW. They have a positive attitude by showing a critical attitude, caring attitude, take responsibility, and support in efforts to prevent VAW. They have sufficient knowledge and attitude, we recommend them to expand their knowledge on VAW and actively take action in preventing VAW in the schools environment and the community.